Pengaruh Tingkat Kecukupan Modal dan Likuiditas Terhadap Return on Asset pada Perusahaan - Sylvalia Puteri; Sutanti (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to further analyze how the level of capital adequacy and liquidity affects the company's return on assets, as well as how optimal strategies can be applied to improve the company's profitability and operational stability in the long term. This research uses data on companies listed on the Indonesia Stock Exchange (IDX), especially those in the technology sector in 2019-2024. This study uses a quantitative method with a causal-comparative research approach. The samples were processed by 20 companies using purposive sampling techniques. The analysis technique used in this study was multiple linear regression with SPSS software. The results showed that capital adequacy and liquidity both had a positive and significant effect on increasing return on assets in technology sector companies listed on the Indonesia Stock Exchange from 2019 to 2024.